Ograniczenia temporalne i deontyczne w modelowaniu procesów biznesowych - Kędzierski, Stanisław (Temporal and Deontic Constraints in Business Process Modelling, 2006)
Business process can be modelled in different ways. Deontic operators augmented with time are one of the most interesting methods of modelling business processes. Deontic operators represent actor's behaviour in business process execution. In this paper a simple method of checking time constraints consistency is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 53-66